CONSTITUTIONAL DESIGN OF LEGAL PROTECTION FOR JOURNALISTS FROM A HUMAN RIGHTS PERSPECTIVE - Brian Hafiz; Arif Hidayat (Law Research Review Quarterly, 2026)
This research aims to analyze the constitutional design of legal protection for journalists in Indonesia from a Human Rights (HAM) perspective. The primary issue addressed is the significant gap between strong constitutional guarantees and the reality on the ground, which reveals high rates of violence and criminalization against journalists. Using a normative legal research method with a statute approach, the results indicate that although Article 28E and 28F of the 1945 Constitution and the ratification of the ICCPR provide a solid normative foundation, current protections remain declarative and lack operational efficacy. This shortfall is caused by regulatory disharmony, where the Press Law is frequently superseded by "elastic clauses" within the ITE Law and the new Criminal Code (KUHP), triggering a chilling effect. Furthermore, the existing protection framework fails to specifically address digital security and gender-based protection. The study concludes that the state, as the duty bearer, must fulfill its due diligence obligations by establishing the Press Law as lex specialis and forming a comprehensive National Protection Mechanism (NPM). Integrating cyber and gender protections is also urgent to ensure press freedom as a pillar of democracy.